Characteristics of cold-sensitive mutants of Escherichia coli K-12 defective in deoxyribonucleic acid replication. - Wehr, C T (1975)
Four cold-sensitive mutants of Escherichia coli have been isolated which show a reduced ability to synthesize deoxyribonucleic acid at low temperature. The mutants also have a reduced ability to incorporate nucleoside triphosphates into deoxyribonucleic acid at low temperature in cell preparations made permeable with toluene. All four mutations are located at or near the dnaA locus on the E. coli genetic map. They are recessive to the wild-type allele and two of them can be integratively suppressed by F episomes.